Peran Satuan Polisi Pamong Praja dalam Penyelenggaraan Ketentraman dan Ketertiban Umum di Wilayah Kecamatan Medan Baru - Berani PA; M. Citra Ramadhan; Ridha Haykal Amal (Mahesa Research Center, 2023)
This study aims to identify and analyze the role of the Civil Service Police Unit, the constraints faced and the policies needed to overcome obstacles related to the role of the Civil Service Police Unit in the Implementation of Peace and Public Order in the Medan Baru District Area. This type of research is normative, namely library research. The nature of this research is analytical descriptive. The results of the study stated that: The role of Satpol PP in maintaining peace and order in the Medan District Area can only be seen in norms, roles as organizations, and roles in the social structure of society. Factors constraining the role of Satpol PP in organizing order and security are: lack of awareness of some people to comply with regulations where compliance only exists when supervised, lack of Satpol PP personnel so that supervision is often constrained, lack of facilities and infrastructure so that they do not support the implementation of tasks, especially policing tasks in the field, as well as the lack of community participation in monitoring their environment so that they do not report violations of regulations that occur. The policy needed is to increase awareness of the order by carrying out outreach to the community, adding Satpol PP personnel, adding facilities and infrastructure, especially those needed in carrying out field assignments, and asking the public to immediately report any violations of the order of conduct that occur in their environment.